Підготовка сировини для виробництва ароматизованої мінеральної води - Любавіна, Олена Олександрівна; Демідова, А. О.; Аксьонова, О. Ф.; Папенко, Г. С. (НТУ "ХПІ", 2015)
У статті наведений аналіз методів та можливих способів підготовки мінеральної води для використання її як сировини для ароматизованого напою. Рекомендується для ароматизації напою виготовляти екстракти з рослинної сировини. Наводиться технологія одержання екстрактів методом мацерації. Представлено структурну технологічну схему приготування ароматизованого напою.

The article provides an analysis of the methods and possible ways of preparing mineral water to use it as a raw material for a flavored drink. Recommended for flavoring beverage use extracts from plant material. Were offered rational conditions for the extraction of aromatic raw materials. We investigated the organoleptic and physico-chemical characteristics of extracts from the leaves of mint and thyme. Provides technology for obtaining extracts by maceration. Is a block flow diagram of obtaining flavored drink. Mineral water "Berezovska" characterized by a specific underground microflora, which has medicinal properties and is in equilibrium with the biologically active organic compounds. This microflora is killed by ultraviolet radiation used in the production of water. The studies provide an opportunity to recommend no UR-disinfection. Was offered the technology preparation of flavored drinks.
Preparation of raw materials for the production of flavored mineral water
Keywords: мінеральна вода; нестабільні сполуки; фільтрування; ароматизовані напої; фітодобавки; безалкогольні напої; виробництво напоїв; mineral water; volatile compound; filtration; degreasing; flavored beverages; antioxidants